Fabrication of polysulfone membrane : the effect of cooling process - Masduki, Mohammad Syafiq (2006)
Three pieces of polysulfone membrane were fabricated by using phase inversion method. In this study, only one parameter was investigated to observe the effect of the parameter on the membrane performance. The parameter that was investigated is the temperature of water bath during the fabrication process of polysulfone membrane. All the membranes were characterized by this technique: modeling of the rejection of sample red colour solution. The interpretation of experiment data was carried out by flux and rejection. In membrane characterization, the important parameter is the optimum temperature in producing the membrane. The result for this project are higher temperature of water bath will produce a more effective polysulfone membrane. However, it must be a limit to prevent the destroyed of polymerization membrane.